PENGARUH NILAI EKSPOR DAN NILAI TUKAR MATA UANG RUPIAH (KURS) TERHADAP PERTUMBUHAN EKONOMI DI JAWA TENGAH - Liris Chrismadana; Sugiyanta Sugiyanta; Achmad Zaenuddin (JOBS (Jurnal Of Business Studies), 2015)
The research aims at knowing how influence of exports value and the Indonesian rupiah exchange rate to the economic growth in Central Java. This research uses multiple linear regression analysis with annual data year 1984-2013 and uses secondary data from government institution in Central Java. The data collect used a literature review. Partially, the independent variable of the export value give a significant effect on economic growth in Central Java. Partial regression test (t test) showed that H0 accepted and Ha rejected contained in the export value variable (X1). While the variable currency exchange rates also has a significant impact on economic growth in Central Java. Partial regression test (t test) showed that H0 accepted and Ha rejected contained in the export value variable (X2) but the exchange rate have influence negatif to the economic growth in Central Java. Simultaneously, the two independent variables significantly influence the economic growth in the province of Central Java.For the coefficient of determination value R Square (R2) of 0.634, which means 63.4% economic growth in Central Java Province can be explained by two Independent variables export and currency exchange rate While the remaining 36.6% is explained by other causes.